Numerical Simulation of the Volumetric Strain Distribution of a Protected Coal Seam - Hengyi Jia (Geofluids)
To investigate the deformation characteristics of protected coal seams, the numerical simulation of the mining of an upper protective coal seam was carried out in the present study. Based on the basic definition of strain, a method for the extraction of the strain data of the protected coal seam was proposed, and the strain distribution characteristics were obtained. It was found that the x-direction strain is mainly distributed near the coal pillars on both sides and inside the goaf, the y-direction strain is mainly distributed at the working face, the initial mining line, and inside the goaf, and the z-direction strain is mainly distributed at the working face, the initial mining line, the coal pillars on both sides, and inside the goaf. The distribution characteristics and the value of volumetric strain were found to be basically consistent with the z-direction strain. As the working face advances, the protected coal seam undergoes compression and damage expansion in turn. The turning point between compression and damage expansion is approximately 15 m in front of the working face. The variation law of gas drainage in the boreholes of the protected coal seam is closely related to the distribution characteristics of volumetric strain. The results of this research are of great significance for the comprehensive investigation of the effects of pressure relief and the permeability enhancement of protective coal seam mining.